Investigating the Use of Interactive Storytelling in Enhancing Oral Skills for Secondary School Students in Indonesia - Saiful, Sri Hastuti Novila Anggraini (Jurnal Kreatif Online, 2020)
English subject in Secondary School demands the students to master both receptive and productive skills. However, the students still face some difficulties in using the skills, they have no courage to speak English in the classroom. The fact shows that teachers mostly prefer to focus on teaching technical aspects rather than communicative aspects of English. As a consequence, students have fewer opportunities to use the language and consider grammar as the key point in learning English. However, the most important thing of learning English is not only about knowing the grammatical rules, but also being able to use the language for communicative purpose. Hence, it is needed to find a solution regarding to this problem. Furthermore, this research aims at finding out the effectiveness of the use of interactive storytelling in the classroom. The investigation is done through reviewing a range of related literature. This research found out that teachers can use Interactive Storytelling which can develop students’ abilities through social interaction and Information Communication and Technology (ICT). The use of interactive storytelling also enables students to gain more practical speaking since it involves more on enhancing collaborative learning, developing creative thinking skills and having a meaningful learning. Despite the benefits, there will be some challenges that need to be considered in applying this method such as large number of students, time allocation, school facilities and teachers’ competency. However, these problems can be solved through conducting teacher professional development program in terms of theoretical and practical teaching, classroom management, teaching strategy, and ICT.